Mendelian CNV mutations - Vermeesch, Joris (Henry Stewart Talks, 2009)
Copy number variation has now been shown to be a major cause of human genetic variation, It has been implicated as the main cause of mental retardation disorders, The boundary between benign and malignant copy number variations is blurring, This is because certain CNVs can be benign but cause genetic disorders dependent on copy number state, sex and genetic background, We coin them "Mendelian CNVs", An overview of autosomal recessive, dominant, X-linked and imprinted CNVs, Diagnostic and clinical consequences